2018
DOI: 10.3390/su10061945
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Activation of Inner Space Components in Sustainable Interior Design

Abstract: Implementation of environmental responsibility issues into the interior design methodology considers many aspects of the design process, but analyzes them separately. These include building materials' and products' specifications based on the assessment of their parameters impact on the users of indoor environments, or resource management within an ecological efficiency context. This concept paper concentrates on the analysis of an environmental activation of inner space components, identified by the author as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 8 publications
0
11
0
1
Order By: Relevance
“…There are differences in people's mental feelings towards the products in an environment, and their demand for a favorable shape of an object could be revealed by context awareness [7]. The results of the literature [8] showed that it was continuable and sustainable to optimize user experience in an environment through upgrading the design level of the components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are differences in people's mental feelings towards the products in an environment, and their demand for a favorable shape of an object could be revealed by context awareness [7]. The results of the literature [8] showed that it was continuable and sustainable to optimize user experience in an environment through upgrading the design level of the components.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The reported effects of CC on the built environment included increasing thermal discomfort, flooding/urban drainage, and damage to infrastructures. In the future, buildings with reduced carbon dioxide emissions, improved ventilation, and those that provide a highquality indoor environment, are imperative towards a sustainable built environment (Celadyn, 2018;Sojobi and Zayed, 2021). In addition, weather data is also required to evaluate how water delivery systems and urban drainage would function in future (Ezeabasili and Okonkwo, 2013).…”
Section: Most Published Categories Across States and Regionsmentioning
confidence: 99%
“…M. Keladuna (Celadyn, 2018) pētījumā aktualizē vides atbildības jautājumu vides resursu pārvaldības kontekstā, kas ietver interjera dizaina projektēšanas integrēšanu ilgtspējīgas apkārtējās vides radīšanai, izmantojot holistisku un sistēmisku dizaina modeli.…”
Section: Criteria For Evaluation Environmental Sustainabilityunclassified